Global and regional needs, unmet needs and access to hearing aids. (3rd March 2020) - Orji, Aislyn; Kamenov, Kaloyan; Dirac, Mae; Davis, Adrian; Chadha, Shelly; Vos, Theo
Abstract: Objectives: This article aims to estimate the global and regional needs, unmet needs and access to hearing aids, as well as the morbidity that can be averted by their use. Design: The study was based on Global Burden of Disease data. Study sample: Hearing impaired individuals "in need" of a hearing aid were defined as those in the moderate, moderately severe, and severe categories. Results: Globally, 401.4 million people are 'in need' of hearing aids. The large majority (83%) of them do not use hearing aids, with higher levels being in some regions such as the African region (90%). Accounting for hearing aid coverage reduced morbidity by 14.6% (95% UI 13.1- 16) – from 25 million YLDs to 21.3 million YLDs. It was estimated that if every single prevalent case in need would use a hearing aid, the burden of disease in this population would be reduced from the untreated 25 million YLDs to 10.3 million YLDs – a reduction of 59%. Conclusions: Development of innovative low-cost technologies with effective service delivery models, policy and regulatory changes to improve access, and combatting the stigma and lack of awareness are some of the potential solutions to improve access to hearing aids.